Compressive Strength and Static Modulus of Elasticity of Periwinkle Shell Ash Blended Cement Concrete - Umoh, Akaninyene Afangide; Olusola, Kolapo O. (International Journal of Sustainable Construction Engineering and Technology, 2012)
The study examined the effect of periwinkle shell ash as supplementary cementitious material on the compressive strength and static modulus of elasticity of concrete with a view to comparing it’s established relation with an existing model. The shells were calcined at a temperature of 800oC. Specimens were prepared from a mix of designed strength 25N/mm2. The replacement of cement with periwinkle shell ash (PSA) was at five levels of 0, 10, 20, 30 and 40% by volume. A total of 90 cubical and cylindrical specimens each were cast and tested at 7, 14, 28, 90, 120 and 180 days. The results revealed that the PSA met the minimum chemical and physical requirements for class C Pozzolans. The compressive strength of the PSA blended cement concrete increased with increase in curing age up to 180 days but decreased as the PSA content increased. The design strength was attained with 10%PSA content at the standard age of 28 days. The static modulus of elasticity of PSA blended cement concrete was observed to increase with increased in curing age and decreases with PSA content. In all the curing ages 0%PSA content recorded higher value than the blended cement concrete. The statistical analysis indicated that the percentage PSA replacement and the curing age have significant effect on the properties of the concrete at 95% confidence level. The relation between compressive strength and static modulus of elasticity fitted into existing model for normal-weight concrete.